Trends in Prostate Cancer Incidence, Hospital Utilization and Surgical Procedures, Canada, 1981–2000 - Neutel, C. Ineke (Can J Public Health, 2006)
Background: Numbers of new prostate cancer cases in Canada continue to increase because of increasing prostate cancer incidence, population growth, aging of the population, and earlier detection methods such as PSA (prostate-specific antigen) testing. Concern has been expressed that PSA-related increases in incidence will make unaffordable demands on Canadian hospital resources. Our objective is to relate increases in prostate cancer incidence to trends in hospitalizations and in- patient treatment. Methods: Hospitalizations with prostate cancer as primary diagnosis were obtained from the Hospital Morbidity Database, estimates of prostate cancer day surgery from the Discharge Abstract Database, newly diagnosed cases from the Canadian Cancer Registry, and prostate cancer deaths from the Vital Statistics Mortality Databases — all for the years 1981–2000. Results: Between 1981–2000, the number of new cases rose from 7,000 to 18,500 with a transient peak, 1991–1994. Hospitalizations rose parallel to the incidence until 1991 but then fell sharply in spite of further increasing incidence. The use of radical prostatectomy (RP) increased steadily, but transurethral prostatectomy and bilateral orchiectomy decreased in the 1990s. Decreases in length of stay and in number of hospitalizations resulted in considerably decreased annual hospital days for all prostate cancer in-patient procedures except RP, which remained level since 1993. Conclusions: A net decrease in number of in-patient days occurred, despite the increasing number of new prostate cancer cases and the increasing use of radical prostatectomy. We concluded that increases in hospital utilization due to early detection programs, such as PSA testing, are unlikely to overwhelm in-patient services of Canadian hospitals.